Methodology Of Teaching English to Preschool Children - Shaymardanova Sarvinoz Khurramovna; Abduvahobova Sevara Bakhtiyarovna (Genius Journals, 2021)
In the last few years, learning a foreign language has become a necessity, not a way of selfimprovement. Foreign language has become a mandatory component of education not only in schools and universities, but also in many additional preschools. The demand for a foreign language in society, on the one hand, as well as the understanding by parents that language is not only a factor in the upbringing of modern man, but also the basis of his social and material well-being in society - on the other hand. this moment is especially popular and relevant for early learning of a foreign language. This article discusses the methods of teaching English to children in preschool education.
Keywords: Preschool education; English language teaching; methodology; psychology